2017
DOI: 10.1007/s40520-017-0739-2
|View full text |Cite
|
Sign up to set email alerts
|

Activities of daily living at different levels of renal function in elderly hospitalized heart failure patients

Abstract: In elderly hospitalized HF patients, the motor ADL recovery process in the low RF group was delayed compared to the high RF group. Cognitive ADL in hospitalized HF patients is difficult to recover, especially in those with low RF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…For all three formulas, the lower the eGFR, the shorter the distance walked by the patient during the 6-minute-test period. Kitamura et al [23] also reported an association between the daily level of motor activity and kidney function. As in the study by Zamora et al [9], no significant association was found in the present cohort between renal function and echocardiographic parameters, irrespective of the used formula.…”
Section: Discussionmentioning
confidence: 94%
“…For all three formulas, the lower the eGFR, the shorter the distance walked by the patient during the 6-minute-test period. Kitamura et al [23] also reported an association between the daily level of motor activity and kidney function. As in the study by Zamora et al [9], no significant association was found in the present cohort between renal function and echocardiographic parameters, irrespective of the used formula.…”
Section: Discussionmentioning
confidence: 94%
“…As predicted, the incidence of CA-AKI is increasing with the decline in BI scores. The decline in ADL is often accompanied by old age, organ dysfunction and increased comorbidities, such as diabetes and hypertension [23][24][25] . Advanced age is well recognized as a negative prognostic marker for CA-AKI [26,27] .…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers reported an association between reduced ADL and changes in biochemical results, including serum albumin level . In a study of 262 geriatric patients, 80% with lower ADL showed hypoalbuminaemia .…”
Section: Discussionmentioning
confidence: 99%